Prevalence and Causes of Blindness and Low Vision in Khuzestan Province, Iran - Feghhi, Mostafa (Ophthalmic Research Center, 2009)
PURPOSE: To determine the prevalence and causes of blindness and low vision in Khuzestan province, Iran in 2006. METHODS: This population-based cross-sectional study included residents of Khuzestan province during the year 2006. The study was designed according to World Health Organization (WHO) recommendations. Multi-stage proportionate clustered random sampling was employed. Sample size was calculated according to the latest national census and estimated rates of blindness. Initially data accumulation including general information and optometrists’ findings was performed at local health centers, followed by referral of subjects with best-corrected visual acuity less than 20/60 for a comprehensive ophthalmologic examination. Categorization of blindness and low vision was based on WHO criteria and causes of visual impairment were classified according to the International Classification of Diseases version 10. RESULTS: Overall, 6,960 subjects with mean age of 24.7±18.3 years (range 3 months to 87 years) participated in the study (74.5% response rate). The prevalence of bilateral blindness and low vision in subjects older than 5 years was 1.3% and 2.6%, respectively;a significant positive trend was observed with increasing age (P<0.001) but no significant correlation was noted with sex and domicile. The leading causes of visual impairment included cataracts (39.0%), refractive errors (37.9%) and amblyopia (23.6%).A minority of cases were due to surgical complications (1.9%) and trauma (1.3%). CONCLUSION: Blindness and low vision in Khuzestan province occurred at an average rate as compared to similar countries. It is estimated that there are 28,537 and 105,995 cases of bilateral blindness and low vision respectively in this province.